Sequential Logic of Polarity Determination during the Haploid-to-Diploid Transition in Saccharomyces cerevisiae - Zapanta Rinonos, Serendipity (Eukaryot Cell, 2014)
In many organisms, the geometry of encounter of haploid germ cells is arbitrary. In Saccharomyces cerevisiae, the resulting zygotes have been seen to bud asymmetrically in several directions as they produce diploid progeny. What mechanisms account for the choice of direction, and do the mechanisms directing polarity change over time? Distinct subgroups of cortical “landmark” proteins guide budding by haploid versus diploid cells, both of which require the Bud1/Rsr1 GTPase to link landmarks to actin. We observed that as mating pairs of haploid cells form zygotes, bud site specification progresses through three phases. The first phase follows disassembly and limited scattering of proteins that concentrated at the zone of cell contact, followed by their reassembly to produce a large medial bud. Bud1 is not required for medial placement of the initial bud. The second phase produces a contiguous bud(s) and depends on axial landmarks. As the titer of the Axl1 landmark diminishes, the third phase ultimately redirects budding toward terminal sites and is promoted by bipolar landmarks. Thus, following the initial random encounter that specifies medial budding, sequential spatial choices are orchestrated by the titer of a single cortical determinant that determines whether successive buds will be contiguous to their predecessors.